Development and performance optimization of a new composite sealing material prepared by drilling cuttings - Li, Xiaoping; Han, Guoping; Wang, Yong; Xu, Jie; Du, Jie; Yang, Bo; Zhang, Min; Li, Tao; Li, Bo; Zhang, Junxiang (Frontiers in Earth Science, 2023)
A highly efficient composite sealing material was prepared using drilling cuttings as the base material and a binder, a coagulant, and other additives as auxiliaries. A four-factor, three-level orthogonal test was designed based on the response surface method (RSM), and a response surface regression model was constructed using compressive strength, fluidity, expansion rate, and setting time as performance indexes to analyze the effects of each factor on material performance and optimize the material proportion. The samples were prepared by simulating the grouting process, the permeability of the samples was measured, and the sealability of the material was verified by analyzing the material microscopic morphology. Results showed that the regression model had a high level of confidence and accuracy and could predict the test results accurately within the range of the test. The effects of the interaction between factors on material performance were also examined. The low permeability of the sealing material samples verified the material’s feasibility. Gradual optimization of material performance revealed that the optimal proportion was 52.6% drill cuttings, 44.3% binder, 0.6% coagulant promoter, and 2.5% expansive agent. Under these conditions, the error between the predicted and test values of each material property was less than 5%, and the comprehensive performance was superior. These findings verify the accuracy of RSM and its applicability to the optimization of material performance. This work provides reasonable theoretical guidance for the preparation of drilling cuttings composite (DC) materials in practical engineering.